Influence of Rhizospheric Bacteria on Growth and Metal Uptake of Heavy Metal Accumulating Plants-A Review - Ramesh, Thanusree Mallakuntla; Kumar Gurajala, Hanumanth; Mopati, Rupadevi; Dulla, Esther Lebonah; Jasti, Pramodakumari (International Journal of Scientific Research in Biological Sciences, 2019)
Rhizosphere microorganisms harbour the plant accumulators and contribute to the metal extraction process. Out of bacteria and fungi, bacteria were more tolerant to heavy metals than fungi. A variety of bacteria growing in metalliferous soils helps to accumulate metals in plants in their harvestable parts and have the potential to be used for remediation of heavy metal polluted lands called plant-assisted bioremediation. The present review focuson examining the current concepts and published data on the role of rhizosphere processes, heavy metal pollution, degradation,role of rhizodeposits, plant hormones, plant secondary metabolites, siderophores and carboxylic acids and conclude with major controls that may be used for their management in plant-assisted bioremediation.